The Influence of Price and Brand Image on Purchasing Decisions for Contemporary Segarkhan Ice Drink in Central JakartaThe Influence of Price and Brand Image on Purchasing Decisions for Contemporary Segarkhan Ice Drink in Central Jakarta - Hermawan, Rudianto; Kusyeni, Raden; Saifullah, Saifullah; Prasioni Untari, Novelita; Sumarna Sobari, Indra (JAMBIS : Jurnal Administrasi Bisnis, 2024)
Currently, drinking contemporary Drink is not just enjoying the dish but also enjoying the atmosphere of the contemporary Drink shop. Now contemporary Drink shops can be used to meet with friends, hold work meetings, do assignments or just fill in spare time. The trend of drinking contemporary Drink has penetrated the city of Jakarta, especially North Jakarta. Of the many contemporary Drink shops in North Jakarta, Segarkhan Ice Drink is one of them. This research was conducted with the aim of analyzing the effect of price and brand image on purchasing decisions (a case study on Segarkhan Ice Drink, Jakarta). The variables in this study consist of price and brand image as the independent variables and purchasing decisions as the dependent variable. This research uses quantitative methods. The population in this study were visitors to contemporary Segarkhan ice drink in March 2024 with a total of 4,372 visitors. The sample was determined using the slovin formula and a total of 190 people were obtained, so the respondents used in this study were 190 people. The sampling technique used was non- probability sampling in the form of purposive sampling. Testing the data using multiple linear regression analysis. T test and F test. The price variable has a positive and significant effect on purchasing decisions, with a regression value of 0.834, t test of 6.667>1.190 Sig. 0.00 <0.05 and the coefficient of determination is 0.714 or 71.4%. The brand image variable has a positive and significant effect on purchasing decisions, with a regression value of 0.782, at-test of 5.142> 1.190 Sig.0.00 <0.05 and the coefficient of determination is 0.665 or 66.5%. Simultaneously price and brand image have a positive and significant effect on purchasing decisions, the f test is 115.151> 2.70 Sig. 0.00 <0.05 with a coefficient of determination of 0.779 or 77.9%.